A Chiral 3 D Net with 2 D Cairo Pentagonal Tiling Projection in Site‐Modified CuCN/CuSCN Networks. Issue 8 (11th May 2016) - Lin, Shi‐Hong; Li, Mian; Luo, Dong; Zhang, De‐Xiang; Wen, Tian; Zhou, Xiao‐Ping; Li, Dan
Abstract: A novel isohedral 3‐periodic net (i.e. a net with one kind of tile), showing a Cairo pentagonal tiling projection on the Euclidean plane, has been identified in a series of site‐modified CuCN/CuSCN networks, namely, [Cu6 (SCN)2 (CN)6 ⋅Ni(tpy)2 ] n (1 ), [Cu6 (SCN)(CN)7 ⋅Ni(tpy)2 ] n (2 ) and [Cu6 (CN)8 ⋅Ni(tpy)2 ] n (3 ) (tpy=2, 2′:6′′, 2′′‐terpyridine). These infinite inclusion compounds were prepared via a solvothermal sulfur migration reaction with subtle modification to fine‐tune the sulfur content. The chiroptical activity of single crystals, which arises from the intrinsically chiral net, was confirmed by X‐ray diffraction and solid‐state circular dichroism spectra. Abstract : The long and winding road : A three‐ dimensional counterpart of the 2 D Cairo pentagonal tiling underlies the crystalline coordination network found in a series of site‐modified CuCN/CuSCN networks (see picture).